Mining Creativity Research to Inform Design Rationale in Open Source Communities - Burleson, Winslow; Tripathi, Priyamvada (Human Technology, 2011)
Design rationale can act as a creativity support tool. Recent findings from the field of creativity research present new opportunities that can guide the implementation and evaluation of design rationale’s ability to foster creative processes and outcomes. By encouraging the exploration of failure through use of analogy, design rationale can foster creative transfer and enable progress in new directions. Open source communities offer an opportunity to observe a form of intrinsically motivated ad hoc design rationale, exhibiting formal and informal information transfer links within forums and allowing access to common tools, expertise, and mentorship. A discussion of a spectrum of implementations of design rationale informs strategies to mitigate conflicts and advance inherent synergies between design rationale and creativity.